2011
DOI: 10.5194/bg-8-2947-2011
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen uptake by phytoplankton in the Atlantic sector of the Southern Ocean during late austral summer

Abstract: Abstract. As part of the Bonus-GoodHope (BGH) campaign, 15 N-labelled nitrate, ammonium and urea uptake measurements were made along the BGH transect from Cape Town to ∼60 • S in late austral summer, 2008. Our results are categorised according to distinct hydrographic regions defined by oceanic fronts and open ocean zones. High regenerated nitrate uptake rate in the oligotrophic Subtropical Zone (STZ) resulted in low f -ratios (f = 0.2) with nitrogen uptake being dominated by ρurea, which contributed up to 70 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
42
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 71 publications
8
42
1
Order By: Relevance
“…Furthermore, the radionuclides derived export production (e.g. 234 Th / 238 U) showed that the transfer rate of carbon to the mesopelagic zone was quite low in this domain (Planchon et al, 2012), consistent with a low new production (Joubert et al, 2011), and probably leading to the relative accumulation of particulate organic N and C observed in the subtropical region (Fig. 5).…”
Section: Biogeochemical Features Of the Subtropical Domain And Its Comentioning
confidence: 61%
See 2 more Smart Citations
“…Furthermore, the radionuclides derived export production (e.g. 234 Th / 238 U) showed that the transfer rate of carbon to the mesopelagic zone was quite low in this domain (Planchon et al, 2012), consistent with a low new production (Joubert et al, 2011), and probably leading to the relative accumulation of particulate organic N and C observed in the subtropical region (Fig. 5).…”
Section: Biogeochemical Features Of the Subtropical Domain And Its Comentioning
confidence: 61%
“…It is likely that the ammonium which is kept at low value here was rapidly taken up. Oligotrophic conditions were further supported by 15 N incubation experiments which showed that the new production rate was low in this domain, unlike the regenerated production, as exemplified by a f-ratio of 0.24 compared to f-ratios of 0.41-0.49 south of this domain (Joubert et al, 2011). PIC and BSi concentrations were extremely low in this area, indicating that the biomass resulted from non-mineralizing phytoplankton.…”
Section: Biogeochemical Features Of the Subtropical Domain And Its Comentioning
confidence: 80%
See 1 more Smart Citation
“…were the most abundant phytoplankton groups in the subtropical domain (Beker and Boye, 2010). This domain also featured oligotrophic conditions (Le Moigne et al, 2012) and relatively high regenerated production (Joubert et al, 2011), which leads us to think that cyanobacteria may also have been present. Cyanobacteria are often too small to be recognized clearly in light-microscope studies.…”
Section: Cycle Of the Organic Ligands Along The Sectionmentioning
confidence: 99%
“…The PlankTOM10.2 biogeochemical model coupled with the two N 2 O submodels is incorporated into the ocean general circulation model NEMO v3.1 (Madec, 2008) Simulations were run to 2014, forced with daily atmospheric conditions from the NCEP reanalysis (Kalnay et al, 1996; for details see Buitenhuis et al, 2013a). Results are reported averaged over the last 5 years.…”
Section: N 2 O Productionmentioning
confidence: 99%